Development of Soil Co-Culture System for Ferulic Acid Production - Kamaliah, Abdul Samad; N., Zainol; Nur Syahirah, Mohd Shkuri (Asian Research Publishing Network (ARPN), 2016)
Ferulic acid is covalently linked with variety of ester bond in plant cell wall make it challenging to be released naturally. Therefore, appropriate fermentation technique with co-culture could be an effective way to produce ferulic acid. The aims of this research were to develop the co-culture system and to evaluate their performance in releasing ferulic acid. Highest production of ferulic acid from banana stem waste as their sole carbon source was found in co-culture of Bacillus cereus CCM 2010, Bacillus pumilus SAFR-032 and Bacillus thuringiensis Bt407. The co-culture was successfully increased 2.6-fold production compared to single culture in 24 hours period of fermentation. Production of ferulic acid were being consistent each production simply by maintaining the quality of the co-culture. The result of this study suggests that synergistic work by co-culture represents a significant role in manufacturing of valuable product through fermentation of agricultural waste.